Assessment of antibiotic- and disinfectant-resistant bacteria in hospital wastewater, south Ethiopia: a cross-sectional study - Sintayehu Fekadu; Yared Merid; Hunachew Beyene; Wondu Teshome; Solomon Gebre-Selassie (Journal of Infection in Developing Countries)
Introduction: Large quantities of antimicrobials are used in hospitals for patient care and disinfection. Antibiotics are partially metabolized and residual quantities reach hospital wastewater, exposing bacteria to a wide range of biocides that could act as selective pressure for the development of resistance. Methodology: A cross-sectional study was conducted between December 2010 and February 2011 on hospital wastewater. A total of 24 composite samples were collected on a weekly basis for bacteriological analysis and susceptibility testing. Indicator organisms and pathogenic and potentially pathogenic bacteria were found and isolated on selective bacteriologic media. Disinfectant activity was evaluated by use-dilution, and minimum inhibitory concentration (MIC) was determined by the agar dilution method. Similarly, antibiotic susceptibility tests were performed using the Kirby-Bauer disk diffusion method. Results: Pathogenic (Salmonella, Shigella, and S. aureus) and potentially pathogenic (E. coli) bacteria were detected from effluents of both hospitals. Dilution demonstrated tincture iodine to be the most effective agent, followed by sodium hypochlorite; the least active was 70% ethanol. MIC for ethanol against S. aureus and Gram-negative rods from Yirgalem Hospital (YAH) showed 4 and 3.5 log reduction, respectively. Salmonella isolates from YAH effluent were resistant to ceftriaxone, tetracycline, and doxycycline. Isolates from Hawassa University Referral Hospital (HURH) effluent were resistant to the above three antibiotics as well as gentamycin. Conclusions: Hospital effluents tested contained antibiotic-resistant bacteria, which are released into receiving water bodies, resulting in a threat to public health.